Analisis Aksiologi Filsafat Pendidikan Islam dalam Penguatan Pendidikan Karakter Peserta Didik di SMP IT At-Taqwa Grabag Magelang - M. Nur Saefullah; Mujiburrohman Mujiburrohman (Lembaga Yasin AlSys, 2026)
Strengthening character education has become an urgent need amid the moral and social challenges faced by students in the modern era. In this context, Islamic educational philosophy, particularly from an axiological perspective, provides a value foundation oriented toward the formation of noble morals, responsibility, discipline, honesty, and social care. This study aims to analyze the implementation of axiological values in Islamic educational philosophy in strengthening students’ character education at SMP IT At-Taqwa Grabag Magelang. This study employed a qualitative approach with a case study design. Data were obtained through in-depth interviews, participatory observation, and documentation studies involving the principal, teachers, and students. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was tested using source and technique triangulation. The results show that the axiological values of Islamic educational philosophy were implemented through the integration of character values into learning, habituation of worship, teacher role modeling, strengthening of Islamic school culture, and extracurricular activities based on character development. This implementation contributed to the formation of religious, disciplined, honest, responsible, and socially caring character. The conclusion of this study emphasizes that the axiology of Islamic educational philosophy has a strategic role in strengthening students’ character education through the internalization of Islamic values integrated into all educational activities. The implications of the study include theoretical contributions to the development of Islamic educational philosophy studies and practical implications for schools in formulating policies and learning models oriented toward strengthening character based on the philosophical values of Islamic education.